Constraints Faced by Rice-Wheat Growers in Training Imparted by KVKs - Tiwari, Anand Kumar; Pathak, Jagannath (Indian Journal of Extension Education, 2011)
Use of modern inputs and adoption of technology in Rice – wheat production are undoubtedly more important in increasing the Rice – wheat productivity. Research evidences shows that the adoption of recommended production technologies gives higher production, consequently more income to the farmers. But the extent of adoption of recommended technologies by the farmers depends upon various factors as well as constraints faced by them. Constraints refer to the item of difficulties faced by trainees. Kvks are grass root level institution imparting training programme for the rural people. Undoubtedly training helping in improving the knowledge and changing in skill. But during the training programme beneficiaries facing many types of constraints. Therefore a study was carried out during 2008-2010 in U.P. of three Kvks viz, Chirakoot, Balia and Meerut to identify the constraints along with their severity. Results of study revealed that, uneconomic land holding (mean score 2.383), nature of training (mean score 2.204), most of training are unsuitable for small and marginal farmers (mean score 2.51) and at the time of training the basic needs of the farmers do not kept in mind (mean score 2.75) were the top most (ranked Ist) constraints faced by Rice – Wheat growers.